Solomon Islands National Information Strategy: To Empower All Communities To Better Manage Their Marine Resources - Eriksson, Hampus (cChange, 2022)
Through the Pacific-European Union Marine Partnership (PEUMP) programme, the Solomon Islands National Information Strategy was developed by cChange, a regional nongovernmental organisation. This National Information Strategy was developed in consultation with the Solomon Islands Ministry of Fisheries and Marine Resources (MFMR) and Ministry of Environment, Climate Change, Disaster Management and Meteorology (MECDM), and its national partners, WorldFish (WF), World Wildlife Fund (WWF-Pacific), and regional partners, the Pacific Community (SPC) and the Locally-Managed Marine Area Network International (LMMA). As outlined in the “Pacific Framework for Action on Scaling-up Community-based Fisheries Management” (2021-2025), a national information strategy is a critical component to upscale community-based management in the Pacific islands. This National Information Strategy endeavors to meet that need.